2015
DOI: 10.1161/circresaha.114.305518
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deficiency of Glutathione S -Transferase P Increases Myocardial Sensitivity to Ischemia–Reperfusion Injury

Abstract: Rationale Myocardial ischemia-reperfusion (I/R) results in the generation of oxygen-derived free radicals and the accumulation of lipid peroxidation-derived unsaturated aldehydes. However, the contribution of aldehydes to myocardial I/R injury has not been assessed. Objective We tested the hypothesis that removal of aldehydes by glutathione S-transferase P (GSTP) diminishes I/R injury. Methods and Results In adult male C57BL/6 mouse hearts, Gstp1/2 was the most abundant GST transcript followed by Gsta4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 62 publications
5
47
0
Order By: Relevance
“…Others have demonstrated that ACR is released after I/R damage in the heart [37] and in the retina of rats [38]. Here, we first demonstrated, to our knowledge, that ACR is the main RCS formed during liver reperfusion in humans.…”
Section: Discussionsupporting
confidence: 50%
“…Others have demonstrated that ACR is released after I/R damage in the heart [37] and in the retina of rats [38]. Here, we first demonstrated, to our knowledge, that ACR is the main RCS formed during liver reperfusion in humans.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, enzymatic conjugation by GSTP facilitates and enhances the detoxification and removal of acrolein and other related aldehydes [52]. The physiological relevance of this metabolic proclivity is supported by studies in rodents that demonstrate a role for GSTP in protection against cardiovascular toxicity of direct acrolein exposure and acrolein-containing tobacco smoke as well as cyclophosphamide-induced urotoxicity and cardiotoxicity, and myocardial ischemia/reperfusion injury [59][60][61][62] . Among all the αβ-unsaturated aldehydes, acrolein is by far the strongest electrophile and reacts 100-fold more rapidly with thiols than 4-HNE [96,97] …”
Section: Gstp and Acrolein Detoxificationmentioning
confidence: 98%
“…GSTP-deficient (GSTPnull) did not show any obvious phenotype, although some null mice had higher body weights than controls [56]. Studies using GSTP-null mice have elucidated GSTP to be an important metabolic determinant of 7,12-dimethylbenz anthracene (DMBA)-induced carcinogenesis [56], APAP-induced hepatotoxicity [57], allergic airways disease [58], tobacco-induced endothelial dysfunction [59], cyclophosphamide-induced urinary bladder and cardio-toxicity [60] and more recently myocardial sensitivity to ischemia-reperfusion injury [61,62]. GSTP was also found to be a major GST isoform in the heart, lung and aorta and contributed significantly to total GST conjugating activity in those tissues.…”
Section: Glutathione S-transferase Pmentioning
confidence: 99%
See 2 more Smart Citations